Thanks for the feedback : the science and art of receiving feedback well (even when it is off base, unfair, poorly delivered, and, frankly, you're not in the mood) /: the science and art of receiving feedback well (even when it is off base, unfair, poorly delivered, and, frankly, you're not in the mood). (2015) - Stone, Douglas, 1958-; Heen, Sheila
No abstract available